Interleukin-18, interleukin-20, and matrix metalloproteinases (MMP-1, MMP-3) as markers of psoriatic arthritis disease severity and their correlations with biomarkers of inflammation and turnover of joint cartilage - Waszczykowski, Michał (Postepy Dermatol Alergol, 2020)
INTRODUCTION: Psoriatic arthritis (PsA) is a chronic, seronegative spondyloarthropathy characterised by joint inflammation and psoriatic skin changes. Recent data indicate that interleukin-18 (IL-18) and interleukin-20 (IL-20) may be involved in the aetiopathogenesis of PsA. AIM: To evaluate the potential role of IL-18, IL-20, and matrix metalloproteinases (MMP-1, MMP-3) in the pathogenesis of PsA and their correlations with other markers of inflammation and destruction of joint cartilage, as well as clinical changes. MATERIAL AND METHODS: The study included 24 patients with PsA and 26 healthy volunteers as a control group. The concentration of IL-18 and IL-20, c-reactive protein (CRP), metalloproteinase-1 and -3 (MMP-1, MMP-3), cartilage oligomeric matrix protein (COMP), aggrecan (PG-AG), and human cartilage glycoprotein (YKL-40) in serum was determined. Clinical severity of the disease according to the BSA, PASI, and DLQI as well as tender and swollen joint count (TJC, SJC) were also evaluated. RESULTS: The concentration of IL-18 was statistically significantly higher in the serum of patients with PsA than in the control group (62.87 pg/ml vs. 16.73 pg/ml, p < 0.0049). Serum IL-20 levels in PsA patients were also higher than in the control group, but without statistical significance (p = 0.2939). The ROC curves showed: AUC = 0.81 for IL-18, AUC = 0.75 for IL-20, AUC = 0.96 for COMP, and AUC = 0.89 for MMP-3. CONCLUSIONS: IL-18 and IL-20 as well as MMP-3 and COMP may be sensitive markers in the diagnosis of PsA.